2007
DOI: 10.1182/blood-2007-02-075036
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CYP3A4 as a predictor of response to chemotherapy in peripheral T-cell lymphomas

Abstract: Peripheral T-cell lymphomas (PTCLs) are aggressive tumors in which the current therapy based on multiagent chemotherapy is not successful. Since cytochrome P450 3A subfamily (CYP3A) enzymes are involved in the inactivation of chemotherapy drugs, we hypothesized that CYP3A and P-glycoprotein (MDR1) expression in these lymphomas could result in a poor clinical response. We measured tumoral CYP3A and MDR1 mRNA content in 44 T-cell lymphomas, finding a large variation in CYP3A expression. Multiplex polymerase chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 25 publications
0
31
0
3
Order By: Relevance
“…Interestingly, all patients with metastasis carried at least more than two unfavorable alleles, suggesting that the genes which were initially selected to be related with the metabolism of doxorubicin and cisplatin might also influence the development of metastasis. For all associated genes in this study we have identified publications suggesting that the expression of these five genes are linked to metastasis formation (20,22,27,30,31). We were able to identify a group of patients with very poor outcome, which may benefit from alternative or novel treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all patients with metastasis carried at least more than two unfavorable alleles, suggesting that the genes which were initially selected to be related with the metabolism of doxorubicin and cisplatin might also influence the development of metastasis. For all associated genes in this study we have identified publications suggesting that the expression of these five genes are linked to metastasis formation (20,22,27,30,31). We were able to identify a group of patients with very poor outcome, which may benefit from alternative or novel treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez-Antona et al (23) found that a high tumoral expression of CYP3A4 was significantly associated with a lower complete remission rate in peripheral T-cell lymphomas (PTCL). They concluded that a high CYP3A4 tumoral expression could be useful to predict poor response to the standard PTCL chemotherapy, but it does not affect survival.…”
Section: Discussionmentioning
confidence: 99%
“…Frozen samples from peripheral T-cell lymphomas were collected through the Spanish National Cancer Centre (Madrid, Spain) tumor bank network from pathology departments of different hospitals in Spain (20). The main characteristics of this human material and cell lines used for mRNA quantification are shown in Supplementary Table S1.…”
Section: Methodsmentioning
confidence: 99%